Penerapan Arsitektur Ekspresionisme pada Perancangan Gedung Pusat Kreativitas Di Kota Kendari - Ferdiansyah Ferdiansyah; Ilham Ilham; Dian Puteri Nurbaity (Jurnal PROYEKSI: Arsitektur dan Perencanaan, 2021)
The creative economy industry is currently starting to develop rapidly in some cities in Indonesia, including Kendari City. Although relatively young, the development of the creative economy in Kendari City is supported by the increasing enthusiasm of young people in this industry. Therefore, to support the interests and talents of the people of Kendari City, especially young people, this study aims to create a place in the form of a Creativity Center Building with the theme of Expressionism. This theme is considered in accordance with the existing conditions in this city which can describe the expression of building users which is reflected in the appearance and interior of the building. This research uses qualitative descriptive and quantitative methods. Based on the analysis of location and site determination, this building is planned to be built in Kadia District with a total area of ​​± 4.34 Ha. The design of the facade /in this building is taken from the form of Kalosara which is a symbol of unity and peace from the Tolaki Tribe, as well as from the logo of the Creative Economy Agency. This form is the result of a study of the theme of Expressionism Architecture. The results of the planning of this building are expected to be a reference for the government in creating a place that can support the economy, especially in the creative industry of Kendari City.